Komprehensif tentang Pengaruh Game Online terhadap Perkembangan Kognitif Sosial dan Emosional Anak-Anak di Era Digital - Saipullah, Saipullah; Putra, Ferdiansyah; Febra Dwi Bahwana; Pratama, Abel Andre; Widodo, Dwi Wahyu; Fitriah, Fitriah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study examines the influence of online gaming on the cognitive, social, and emotional development of children aged 8–12 at the Kasih Sayang Orphanage in Bengkulu. The intervention was conducted over a single day, utilizing educational and participatory observation methods, including interactive presentations, small-group discussions, semi-structured interviews, and observations during multiplayer gaming sessions (Minecraft, Mobile Legends, Free Fire, Clash of Clans). Data were analyzed using a descriptive qualitative approach with thematic coding to categorize participants’ responses and behaviors. The findings reveal that before the intervention, the children tended to engage in excessive gaming, which negatively impacted their direct social interactions and self-regulation. Following the educational session, approximately 68% of the participants expressed a commitment to reducing their gaming duration and demonstrated more cooperative behavior during gameplay. This study highlights the effectiveness of contextual and participatory educational approaches in enhancing children's digital awareness and self-regulation, particularly within vulnerable environments such as orphanages. Therefore, ongoing support and active involvement of caregivers are strongly recommended to foster healthier gaming habits.